Chitosan-Alginate Nanoparticle System Efficiently Delivers Doxorubicin to MCF-7 Cells. (24th August 2016) - Katuwavila, Nuwanthi P.; Perera, A. D. L. Chandani; Samarakoon, Sameera R.; Soysa, Preethi; Karunaratne, Veranja; Amaratunga, Gehan A. J.; Karunaratne, D. Nedra
Abstract : A chitosan-alginate nanoparticle system encapsulating doxorubicin (DOX) was prepared by a novel ionic gelation method using alginate as the crosslinker. These nanoparticles were around 100 nm in size and more stable with higher positive zeta potential and had higher % encapsulation efficiency (95%) than DOX loaded chitosan nanoparticles (DOX Csn NP) crosslinked with sodium tripolyphosphate (STPP). FTIR spectroscopy and thermogravimetric analysis revealed successful loading of DOX. In vitro drug release showed an initial release phase followed by slow release phase with higher cumulative release obtained with DOX loaded chitosan-alginate nanoparticles (DOX Csn-Alg NP). The in vitro cytotoxicity of DOX released from the two nanoparticle systems showed a notable difference on comparison with that of free DOX on the MCF-7 cell line. The SRB assay, AO/EB staining, and fluorescence uptake study indicated that free DOX only showed dose dependent cytotoxicity, whereas both dose and time dependency were exhibited by the two sets of NPs. While both systems show sustained release of DOX, from the cell viability plots, DOX Csn-Alg NPs showed their superiority over DOX Csn NPs. The results obtained are useful for developing DOX Csn-Alg NPs as a sustained release carrier system for DOX.